2015
DOI: 10.1103/physrevlett.115.047601
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Control of Interfacial Ferromagnetism inCaMnO3/CaRuO3Heterostructures

Abstract: New mechanisms for achieving direct electric field control of ferromagnetism are highly desirable in the development of functional magnetic interfaces. To that end, we have probed the electric field dependence of the emergent ferromagnetic layer at CaRuO_{3}/CaMnO_{3} interfaces in bilayers fabricated on SrTiO_{3}. Using polarized neutron reflectometry, we are able to detect the ferromagnetic signal arising from a single atomic monolayer of CaMnO_{3}, manifested as a spin asymmetry in the reflectivity. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…The antiferromagnetic Mott insulator CaMnO3 is a well-established example of a complex transition-metal oxide in which electronic and magnetic properties can be manipulated via strain, heteroengineering and external stimuli [10][11][12][13][14] . A recent theoretical study suggests that, in addition to directly affecting internal bond lengths and oxygen octahedral rotations, coherent epitaxial strain can facilitate spontaneous formation of oxygen vacancies and even influence defect-site preference leading to vacancy ordering in CaMnO3 and similar materials 15,16 .…”
Section: Textmentioning
confidence: 99%
“…The antiferromagnetic Mott insulator CaMnO3 is a well-established example of a complex transition-metal oxide in which electronic and magnetic properties can be manipulated via strain, heteroengineering and external stimuli [10][11][12][13][14] . A recent theoretical study suggests that, in addition to directly affecting internal bond lengths and oxygen octahedral rotations, coherent epitaxial strain can facilitate spontaneous formation of oxygen vacancies and even influence defect-site preference leading to vacancy ordering in CaMnO3 and similar materials 15,16 .…”
Section: Textmentioning
confidence: 99%
“…[146] (b) At low bias (100mV, blue symbols) the minor loop shows the saturation State 1, the high resistance State 2 due to misalignment of magnetic moments of top and bottom layer, and the low resistance 1´ where magnetic moments are aligned along the easy axis of the bottom layer. Notice that high 2 and low 1´ resistance states are stable in zero magnetic field at a temperature of 94 K. [147] (c) Heterostructure and test setup schematics. (d) Spin asymmetry of Sample A after cooling in 700 mT without a bias and with a bias of -400 V, respectively.…”
Section: Other Dielectric Oxidesmentioning
confidence: 99%
“…(d) Spin asymmetry of Sample A after cooling in 700 mT without a bias and with a bias of -400 V, respectively. [147] Direct electric field control of magnetization without multiferroics or magnetoelasticity may also induce magnetoelectric coupling. Grutter et al stimuli.…”
Section: Other Dielectric Oxidesmentioning
confidence: 99%
“…In correlated d -electron heterointerfaces, besides the density ratio n m /n c , the dimensionality and orbital polarization of the magnetic interactions are all vital components for the formation of a ground state as exemplified by the emergent FM at the manganate-cuprates [21,22]and manganite-ruthenate interfaces [23][24][25][26]. Moreover, it has been revealed that due to the significantly enhanced quantum fluctuations in reduced dimensions, under the scenario of Kondo state destruction [7,27,28] the electron and spin degrees of freedom start playing a major role to tune the heavy-fermion metal into a magnetic metal phase by crossing the quantum critical point.…”
mentioning
confidence: 99%